Alegorias psicotrópicas : substâncias psicoativas ilegais, drogas e as imagens contemporâneas de uma praxis milenar - Pinto, Getulio Sérgio Souza (2017)
The field of problems from which the present dissertation emerges is the “terrain” of questions on usage of illegal psychoactive substances in contemporary times and the relationship between a conception of illegal drug as a harm itself and the consequent damage causing to those who experience it. Analyzing the social apparatuses surrounding the infamous War on Drugs, which was erected throughout the twentieth century, it aims at dismantling the discursive procedural apparatus that justifies the imprisonment and exterminating of minorities. Starting from contributions of intercessors such as Nietzsche, Foucault, and Walter Benjamin, the methodology is defined as an essayist allegorism, in which breaking with logocentric and academicist logic in ethical, aesthetic and political dimensions is motor of the deconstruction of totalized images in the field in question. Allegories that are the hybridizating of events and are means used to achieve the objectives of the research. These allegories are not from a specific time, but it is imperative to say that emergence´s moment of the research regards the time when I acted as a psychologist with homeless people. At the same time, genealogical researches are used to situate the political bases of compositing of contemporary knowledge and practices on drugs. In this way, it is intended to constitute the dissertation as a provocative linguistic piece that instigates by a literary praxis the promotion of a new Pathos in this field, other than the fear and repulsion of illegal psychoactive substances. From the promoting of sensations, it is ultimately sought to disrupt the ethos that naturalizes the usage of illegal drugs as unique cause of all the social problems that plagues the cities. To this goal, the stories present in the research focus on moments in which the touching of different realities in field of drugs and the affections, has dismantled prerogatives of kidnapping and exterminating, and the wild featuring of encounters wasn´t subjugated by dictates of the poor technicist discursiveness that had been erected about drugs on twentieth century.